On Employment and Curriculum of the International Business Program - Sun, Emily (Journal of International Business Studies, 1973)
In terms of employment with an international company and entering into the area of international operations of the employer, a survey based on questionnaires suggests that the international business program is more suitable for graduates than undergraduates and for a combined major than a major.